Eye movement programming and reading accuracy. Issue 1 (January 2018) - Inhoff, Albrecht W; Gregg, Julie; Radach, Ralph
Eye movements were measured during the silent reading of sentences to extract several oculomotor measures. Rather than each measure being examined independently, oculomotor responses were grouped into two types, the assumption being that the grouping would project onto underlying constructs. Properties of forward-directed movements were assumed to reflect the success with which linguistic information was acquired (acquisition), and corrective responses were assumed to reveal readers' responding to difficulties (correction). These two types of oculomotor responses were linked to indexes of reading accuracy (accuracy), which were obtained from separate materials so that eye movements with one set of materials could be used to predict reading accuracy for another set of materials. Path analyses indicated that correction, but not acquisition, was linked to accuracy. The additional clustering of acquisition, correction, and accuracy scores identified a group of readers with relatively low accuracy scores. These readers were typical in their acquisition of linguistic information but under-used corrective responding.